The disruptors technology-driven architect-entrepreneurs - Shelden, Dennis; Gehry, Frank O. 1929-; Berkel, Ben van, 1957-; Cramer, James P.; Simpson, Scott|c(Architect); Yuan, Philip F.; Bernstein, Phillip (Phillip Gordon), 1957-; Della Valle, Jared 1971-; Lynn, Greg; Spiller, Neil (Architectural design)
Technology-driven disruption and entrepreneurial response have become profound drivers of change in modern culture. Wholly new organizations have rapidly emerged in many fields including retail, print media and transportation, often dramatically altering both the products and processes that define these industries. Architecture has until now been minimally impacted by this technologically driven upheaval. But there are many signs that this period of tranquility is ending. Startups are proliferating, targeting diverse innovations from environmental performance to large-scale 3D printing. Traditional architecture and engineering firms are creating incubators and spin-offs to capitalise on their innovations. Large and innovative organisations from outside the professions are becoming interested in the built environment as the next platform for technological and economic disruption. These new directions for the discipline will potentially create radically new types of practice, new building typologies, and new ways for both design professionals and societies to engage with the built environment. It is crucial that architectural discourse addresses these possibilities, and begins to embrace technology-driven entrepreneurship as a central theme for the future of architectural practice .